Belgium : Selected Issues. (IMF Staff Country Reports; Country Report ;, 1997)
This Selected Issues paper reviews Belgium's experience with fiscal adjustment and the long-term outlook for the public finances. The paper discusses the composition and scale of the fiscal adjustment, and the extent to which it has exerted a durable impact on the public finances. It offers a quantitative analysis of the interaction between fiscal policy and developments in saving and investment, with a view to contributing to reflection on desirable policy priorities in the future.